Lean Six Sigma in Africa: Fad or real solution of competitiveness? - Mezouari, Said El; Bouaouda, Zahira; Drissi, Hicham (INTERNATIONAL JOURNAL OF MANAGEMENT & INFORMATION TECHNOLOGY, 2013)
Companies tend increasingly to turn to the so-called continuous improvement in order to improve their performance and thus enhance their competitiveness approaches. In times of crisis, the use of these approaches becomes mandatory. In this context, the Lean Six Sigma is incontestably today a vehicle for business development as it allows performance improvement through various appropriate tools on one side, and incitement to contribution of different actors in the company, on the other side. In Africa, the Lean Six Sigma looks like an opportunity that seems to come at the right time in an environment that seems to need it. Is it then a management instrument emerging from a fad phenomena, or is it a real tool for performance improving for African companies, responding to a real need?